2017
DOI: 10.13005/ojc/330136
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Spectroscopic Characterization, Computational Exploration of 6-(2-(2, 4-Dinitrophenylhydrazano)-Tetrahydro-2 Thioxopyrimidin-4(1h)-one

Abstract: The structural and vibrational properties of 6-(2-(2,4-dinitrophenylhydrazano)-tetrahydro-2-thioxopyrimidin-4(1H)-one (3) prepared by condensation of synthesized thiobarbituric acid (1) with 2,4-dinitrophenylhydrazine (2) were studied using experimental FT-IR, FT-Raman, NMR spectra and theoretical calculations based on the density functional method were the simulated spectra coincides with experimental spectra. By means of HOMO-LUMO analysis charge transfer and stability of the molecule is analyzed. The stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Several articles employed the PM3 method in medicinal chemistry research. [ 22 ] The optimized geometries calculated by PM3 were used as strategy to obtain N-Acylhydrazone using the HyperChem 8.0.10 software is represented in Figure1, and the data listed in table 1 showed the highest atomic charge of all NAH derivatives IX-XII. Studies of the stable structures can form a strategy to rationalize important aspects of medicinal compounds.…”
Section: Computational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles employed the PM3 method in medicinal chemistry research. [ 22 ] The optimized geometries calculated by PM3 were used as strategy to obtain N-Acylhydrazone using the HyperChem 8.0.10 software is represented in Figure1, and the data listed in table 1 showed the highest atomic charge of all NAH derivatives IX-XII. Studies of the stable structures can form a strategy to rationalize important aspects of medicinal compounds.…”
Section: Computational Studiesmentioning
confidence: 99%
“…This observation motivated the definition of the Mulliken electronegativity. [29] The physicochemical properties of molecules, such as their lipophilicities and polar surface areas (PSAs) play important roles in determining biological responses and are commonly used to study the structure-activity relationships of bioactive molecules in medicinal chemistry. [30,31] The results showed that derivative XII has a high value for Dipole moment, shown in table 3, 5.544 Debye.…”
Section: μ = -(Ip + Ea)/2mentioning
confidence: 99%